Poultry liver protein hydrolyzate in the diet of tilapia (Oreochromis niloticus) larvae (Research, Society and Development, 2023)
The objective of the present work was to evaluate the performance of Nile tilapia larvae fed with increasing levels of poultry liver hydrolysates. 700 two-day-old larvae were used, distributed in 28 boxes (40 liters), in a completely randomized design with seven treatments and four replications. The treatments consisted of diets with different inclusions of poultry liver hydrolysates: 0 (control), 2, 4, 6, 8, 10 and 12% in isoprotein diets (38% CP). Feeding was carried out six times a day (8; 10; 12; 14; 16 and 18 h). There was no influence of the hydrolyzate on the final weight, final length, final biomass, condition factor and survival of the larvae. Larvae that received diets with 4 and 6% hydrolyzate showed greater standardization in animal weight. It is recommended to use at least 4% of poultry liver protein hydrolyzate, providing greater uniformity of Nile tilapia larvae.